EVA composite sheet and preparation method thereof

Mechanical chemical de-crosslinking of EVA using phosphogypsum powder and antioxidants addresses the recycling challenges of cross-linked EVA, producing composite sheets with improved plasticity and mechanical properties for high-value reuse.

CN119192630APending Publication Date: 2024-12-27FUJIAN HUAFENG NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411355642.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Cross-linked EVA waste is difficult to recycle due to its thermosetting properties, leading to low-value recycling methods and unstable process conditions, and the resulting products lack plasticity for re-molding.

Method used

A method involving mechanical chemical de-crosslinking of waste EVA using phosphogypsum fine powder as a grinding aid, combined with antioxidants, to break cross-linked networks and enhance interaction with the matrix, resulting in a denser structure with improved plasticity and mechanical properties.

Benefits of technology

The method enables the production of EVA composite sheets with enhanced plasticity and mechanical properties, facilitating high-value recycling and reuse of waste EVA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063530330000121
    Figure BDA0005063530330000121
Patent Text Reader

Abstract

The invention relates to an EVA composite sheet and a preparation method thereof. According to the preparation method, waste EVA is subjected to decrosslinking in a mechanochemical decrosslinking mode, and ardealite fine powder and an antioxidant are added. Meanwhile, the ardealite fine powder is also used as a filling agent in the subsequent banburying step, and the interaction between the ardealite fine powder and a matrix is enhanced through the combination of the ardealite fine powder and the decrosslinked EVA active group, so that a more compact structure is formed, the mechanical property of the EVA composite sheet is further optimized, and the efficient recycling of the waste EVA is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material recycling, and in particular to an EVA composite sheet prepared by using recycled EVA and a preparation method thereof. Background Art

[0002] Cross-linked foamed ethylene-vinyl acetate (EVA) has good elasticity and processability, and is often widely used in mid-to-high-end sports shoes in the form of midsoles. However, EVA solid waste will be generated at the end of its life cycle, and it is difficult to recycle it with high value and high efficiency due to its cross-linked chemical bonds and thermosetting properties.

[0003] A common recycling method is to reincorporate waste EVA foam materials as fillers into composite materials or concrete, but this does not bring the same value as virgin EVA. Mechanochemical methods have been widely reported in the recycling of polymer materials. This method has simple processes and convenient operations, and is widely used in actual production. However, the plasticity of the product obtained by this method is difficult to meet the requirements of re-molding processing, and there is a problem of unstable process conditions. Summary of the invention

[0004] In view of the above problems, the present application provides a new method for preparing EVA composite sheets, which uses recycled EVA as raw material, has stable process conditions, and the obtained EVA composite sheets have plasticity that can be re-molded, and are energy-saving and environmentally friendly.

[0005] The first aspect of the present application provides a method for preparing an EVA composite sheet, wherein the preparation of the EVA composite sheet comprises the following steps:

[0006] Pelletizing: Wash and pelletize the recovered waste EVA to obtain EVA pellets;

[0007] Decrosslinking: the EVA particles, phosphogypsum powder and antioxidant are mixed evenly, and added into a rheometer for decrosslinking to obtain a decrosslinking mixture; the decrosslinking temperature is <160°C; the decrosslinking mixture contains decrosslinked EVA and phosphogypsum powder.

[0008] Internal mixing: pure EVA, de-crosslinking mixture, crosslinking agent, stearic acid, zinc oxide and zinc stearate are added into an internal mixer for melting and blending to obtain a mixed rubber material; the internal mixing temperature is less than 160°C;

[0009] Hot pressing: putting the mixed rubber into a flat vulcanizer for hot pressing at a temperature of less than 160° C. to obtain the EVA composite sheet.

[0010] Different from the existing technology, the waste EVA is de-crosslinked by mechanical chemical de-crosslinking, and phosphogypsum fine powder is added as a grinding aid. Under the action of temperature, extrusion and shear deformation, the cross-linked network structure of EVA is destroyed, and antioxidants are added to prevent them from re-crosslinking, synergistically improving the de-crosslinking degree of EVA, so that the de-crosslinked EVA contains smaller polymer chains, and its plasticity and fluidity are greatly improved. At the same time, the phosphogypsum fine powder is used as a filler in the subsequent mixing step. By combining with the active groups of the de-crosslinked EVA, the interaction between it and the matrix is ​​enhanced to form a denser structure, thereby optimizing the mechanical properties of the EVA composite sheet and realizing the efficient reuse of waste EVA.

[0011] Furthermore, in the pelletizing step, the size of the EVA pellets is 2-8 mm.

[0012] Furthermore, in the de-crosslinking step, the phosphogypsum fine powder is prepared by washing and calcining the phosphogypsum and then grinding it, and the mesh size of the phosphogypsum fine powder is 60-80 meshes.

[0013] Furthermore, in the de-crosslinking step, the phosphogypsum fine powder is prepared by washing, calcining, grinding and then modifying the phosphogypsum; the modification treatment includes the following steps: adding the washed, calcined and ground phosphogypsum and stearic acid into water for ultrasonic modification.

[0014] Furthermore, in the de-crosslinking step, the mass ratio of the EVA particles, the phosphogypsum powder and the oxidant is 60-80:20-40:0.5-1.4.

[0015] Furthermore, in the de-crosslinking step, the de-crosslinking temperature is 120-140°C.

[0016] Furthermore, in the de-crosslinking step, the antioxidant is one of Irgafos 168 and Irganox 1010.

[0017] Furthermore, the banburying step includes the following components in parts by weight: 50-70 parts by weight of pure EVA, 30-50 parts by weight of de-crosslinked EVA, 0.8-1.2 parts by weight of a crosslinking agent, 1.0-1.5 parts by weight of zinc oxide, 0.3-0.7 parts by weight of stearic acid, and 0.3-0.7 parts by weight of zinc stearate.

[0018] Furthermore, the banburying step further includes 16-24 parts by mass of SBS.

[0019] Furthermore, in the banburying step, the banburying temperature is 100-120°C.

[0020] A second aspect of the present application provides an EVA composite sheet, which is prepared by the preparation method described in the first aspect of the present application.

[0021] The above-mentioned records related to the invention content are only an overview of the technical solution of the present application. In order to enable ordinary technicians in the field to more clearly understand the technical solution of the present application, and then implement it according to the written contents of the specification, and to make the above-mentioned purpose and other purposes, features and advantages of the present application easier to understand, the specific implementation methods of the present application are explained below. DETAILED DESCRIPTION

[0022] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments.

[0023] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description in conjunction with the specific embodiments listed. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0024] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.

[0025] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.

[0026] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.

[0027] In the present application, terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship of quantity, priority or sequence between these entities or operations.

[0028] Without further limitations, in this application, the words "include", "comprises", "has" or other similar expressions used in the sentences are intended to cover non-exclusive inclusion. These expressions do not exclude the presence of additional elements in the process, method or product including the elements, so that the process, method or product including a series of elements may include not only those limited elements, but also other elements not explicitly listed, or also include elements inherent to such process, method or product.

[0029] Similar to the understanding in the Examination Guidelines, in this application, expressions such as "greater than", "less than", "exceed" and the like are understood to exclude the number itself; expressions such as "above", "below", "within" and the like are understood to include the number itself. In addition, in the description of the embodiments of this application, "multiple" means more than two (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups", "multiple times", etc., unless otherwise clearly and specifically limited.

[0030] The first aspect of the present application provides a method for preparing an EVA composite sheet, wherein the preparation of the EVA composite sheet comprises the following steps:

[0031] Pelletizing: Wash and pelletize the recovered waste EVA to obtain EVA pellets;

[0032] Decrosslinking: the EVA granules, phosphogypsum powder and antioxidant are mixed evenly, and added into a rheometer for decrosslinking to obtain a decrosslinking mixture; the decrosslinking temperature is less than 160° C.; the decrosslinking mixture comprises decrosslinking EVA and phosphogypsum powder;

[0033] Internal mixing: pure EVA, de-crosslinking mixture, crosslinking agent, stearic acid, zinc oxide and zinc stearate are added into an internal mixer for melting and blending to obtain a mixed rubber material; the internal mixing temperature is less than 160°C;

[0034] Hot pressing: putting the mixed rubber into a flat vulcanizer for hot pressing at a temperature of less than 160° C. to obtain the EVA composite sheet.

[0035] In the process of de-crosslinking, phosphogypsum fine powder acts as a grinding aid. Due to its high strength, it can provide additional shear force. By adsorbing on the cross-linked EVA particles, under the action of mechanical force and chemistry, it causes point or line defects, thereby reducing the strength and hardness of the EVA particles. Macroscopically, the EVA particles become softer and smaller, and structurally, the cross-linked body structure is destroyed, and the macromolecules are broken into small molecular segments. In this process, the chemical activity of the de-crosslinked EVA is increased, and the group activity at the end of the molecular chain is increased, and cross-linking polymerization can occur again.

[0036] The bound water in phosphogypsum is a special structure, which generally begins to decompose at about 160°C, while the temperatures of the de-crosslinking, banburying and hot pressing steps are all below 160°C. Therefore, most of the bound water structures in the phosphogypsum of the present invention exist and have a large number of active hydroxyl groups.

[0037] During the mixing process, phosphogypsum powder is used as a filler. During the mixing and mixing process, due to the previous de-crosslinking treatment, the ester bond of EVA is broken, which increases the number of hydroxyl groups (-OH). The bound water in phosphogypsum has a large number of active hydroxyl groups. The increase in active groups in EVA is conducive to its interaction with phosphogypsum to form hydrogen bonds. And through the de-crosslinking treatment, phosphogypsum is more evenly dispersed in the matrix, avoiding the presence of "agglomerated" particles in the de-crosslinked EVA. Therefore, phosphogypsum can be evenly combined with EVA in the mixing step, providing better strength for the composite sheet.

[0038] Different from the prior art, the waste EVA is de-crosslinked by mechanical chemical de-crosslinking, and phosphogypsum fine powder is used as a grinding aid. Under the action of temperature, extrusion and shear deformation, the cross-linked network structure of EVA is destroyed. At the same time, antioxidants are added to prevent them from re-crosslinking, synergistically improving the de-crosslinking degree of EVA, and making the de-crosslinked EVA contain smaller polymer chains, and its plasticity and fluidity are greatly improved. At the same time, phosphogypsum fine powder is used as a filler in the mixing step. By combining with the active groups of EVA after de-crosslinking, the interaction between it and the matrix is ​​enhanced to form a denser structure, thereby optimizing the mechanical properties of the EVA composite sheet and realizing the recycling and reuse of waste EVA.

[0039] Furthermore, the waste EVA is waste EVA sole material.

[0040] Furthermore, the waste EVA soles are derived from EVA midsoles of scrapped sports shoes.

[0041] Furthermore, the cleaning step includes a first water wash, drying and a second alcohol wash. The first wash uses water, the main purpose of which is to wash away the dust and sand of the waste EVA; the second wash uses alcohol with a concentration of 60%-70%, mainly to remove the colloid on the surface of the EVA to facilitate subsequent processing.

[0042] Furthermore, in the pelletizing step, the size of the EVA pellets is 2-8 mm. When the particle size is less than 2 mm, the crushing time is long and the energy consumption is high; when the particle size is greater than 8 mm, there is an adverse effect on the subsequent de-crosslinking of the EVA.

[0043] Furthermore, in the de-crosslinking step, the phosphogypsum fine powder is prepared by washing and calcining the phosphogypsum and then grinding it, and the mesh size of the phosphogypsum fine powder is 60-80 meshes.

[0044] Phosphogypsum is a by-product of phosphorus industrial production. After washing and calcination, on the one hand, the soluble impurities such as phosphorus and fluorine in the phosphogypsum can be reduced, and on the other hand, the strength of the phosphogypsum can be improved, so that the phosphogypsum can provide better strength after being combined with EVA particles.

[0045] Furthermore, the de-crosslinking step, washing, calcining and grinding of phosphogypsum specifically comprises the following steps:

[0046] Water washing: after the phosphogypsum and water are evenly mixed, the mixture is allowed to stand and filtered to obtain the washed phosphogypsum;

[0047] Calcination: calcining the washed phosphogypsum at 350-450°C to obtain calcined phosphogypsum;

[0048] Grinding: Grind the calcined phosphogypsum to obtain 60-80 mesh phosphogypsum fine powder.

[0049] Furthermore, the preparation of the phosphogypsum fine powder also includes a modification step: adding the washed, calcined and ground phosphogypsum and stearic acid into water for ultrasonic modification.

[0050] Water washing: after the phosphogypsum and water are evenly mixed, the mixture is allowed to stand and filtered to obtain the washed phosphogypsum;

[0051] Calcination: calcining the washed phosphogypsum at 350-450°C to obtain calcined phosphogypsum;

[0052] Grinding: Grinding the calcined phosphogypsum to obtain 60-80 mesh ground phosphogypsum;

[0053] Modification: The ground phosphogypsum is placed in distilled water, and stearic acid is added, and then ultrasonically modified at room temperature, filtered, and dried to obtain phosphogypsum fine powder.

[0054] Furthermore, the mass ratio of the phosphogypsum to stearic acid is 1:2-5.

[0055] Furthermore, the mass of the distilled water is 10-20 times the mass of the phosphogypsum.

[0056] Phosphogypsum contains some phosphorus, fluorine, inorganic substances, etc., which lead to performance degradation. Soluble phosphorus is adsorbed on the surface of phosphogypsum, making the structure of phosphogypsum loose and the strength low. Soluble fluorine can coarsen the gypsum crystals, thereby causing low strength. To address this problem, the present invention first washes the phosphogypsum with water to remove the content of harmful impurities such as soluble phosphorus and fluorine, and then calcines it at high temperature to make these undissolved organic matter become insoluble and have a higher structure of calcium phosphate, hydroxyapatite and fluoroapatite, etc., thereby reducing the impact of harmful impurities and improving the strength of phosphogypsum.

[0057] Stearic acid is used to modify the phosphogypsum powder with the aid of ultrasound. Since the molecular structure of stearic acid contains hydrophilic and oleophobic groups, the polar groups in the molecular chain can react with specific functional groups on the surface of phosphogypsum particles to generate stable chemical bonds, which can coat the surface of phosphogypsum and improve its compatibility with EVA. Ultrasonic waves also change the microscopic morphology of phosphogypsum powder particles, so that the subsequent mixing step and the interface with EVA can fit tightly without gaps, which can further improve the mechanical properties of the EVA composite sheet.

[0058] Furthermore, in the de-crosslinking step, the mass ratio of the EVA particles, the phosphogypsum powder and the antioxidant is 60-80:20-40:0.5-1.4.

[0059] In the de-crosslinking step, phosphogypsum powder, antioxidant and EVA particles are mixed for mechanochemical de-crosslinking. In the de-crosslinking process of EVA particles, phosphogypsum powder has the function of a grinding aid, and because of its high strength, it provides additional shearing force. The phosphogypsum powder will be adsorbed on the EVA particles, and under the action of mechanochemical force, it will cause defects of points or lines, thereby reducing the strength and hardness of the EVA particles, which will be manifested as softer and smaller EVA particles in the macroscopic sense, and the cross-linked body structure of EVA will be destroyed in the microstructure, and the macromolecules will be broken into small molecule segments. In this process, the chemical activity of the EVA after de-crosslinking is improved, and the group activity of the molecular chain end is improved, and cross-linking polymerization can occur again. For this reason, the present invention adds an antioxidant to avoid the re-polymerization and cross-linking of the small molecule substances after de-crosslinking, and synergizes to improve the de-crosslinking degree of EVA.

[0060] Furthermore, in the de-crosslinking step, the de-crosslinking temperature is 120-140°C.

[0061] Furthermore, in the de-crosslinking step, the antioxidant is one of Irgafos 168 and Irganox 1010.

[0062] Furthermore, the de-crosslinking is performed using a HAAKE rheometer.

[0063] Furthermore, the banburying step includes the following components in parts by weight: 50-70 parts by weight of pure EVA, 30-50 parts by weight of de-crosslinked EVA, 0.8-1.2 parts by weight of a crosslinking agent, 1.0-1.5 parts by weight of zinc oxide, 0.3-0.7 parts by weight of stearic acid, and 0.3-0.7 parts by weight of zinc stearate.

[0064] Stearic acid in the components is a good processing aid. Its addition can make the material non-sticky to the wall or roller during the plasticization process, which is conducive to mold opening and demolding. However, if it is used in excessive amounts, it will easily cause the system to be too acidic, inactivate the crosslinking agent, and delay crosslinking. Zinc oxide and zinc stearate work together to neutralize the acidic substances in the EVA formula system, creating a weak alkaline environment that is conducive to the chemical reaction; at the same time, it can also be dispersed in the rubber as a heat conductor to make the overall temperature of the rubber consistent, thereby avoiding local burning of the rubber. When heated, the crosslinking agent will release free radicals to activate EVA, causing it to undergo a chemical reaction and crosslink with each other, obtaining a three-dimensional network structure that can improve its rheological properties and physical and mechanical properties.

[0065] Furthermore, the banburying step further includes 16-24 parts by weight of SBS. The addition of SBS can increase the elasticity and softness of the composite material.

[0066] Furthermore, in the banburying step, the banburying temperature is 100-120°C.

[0067] Furthermore, in the banburying step, the cross-linking agent is dicumyl peroxide.

[0068] Furthermore, in the hot pressing step, the hot pressing temperature is 140-150°C.

[0069] A second aspect of the present application provides an EVA composite sheet, which is prepared by the preparation method described in the first aspect of the present application.

[0070] In this embodiment, pure EVA is 100% EVA; the antioxidant used is Irgafos 168; and the cross-linking agent used is dicumyl peroxide.

[0071] Example 1: Preparation of EVA composite sheet

[0072] Granulation: The discarded EVA sole material (EVA midsole after scrapping sports shoes) is washed with clean water for the first time for 20 minutes, and then placed in a blast drying oven for drying; then the EVA sole is crushed into particles with a particle size of 4mm using a crusher, and the EVA particles are washed with 60%-70% alcohol for the second time, and dried to obtain EVA granular materials;

[0073] Preparation of phosphogypsum fine powder: phosphogypsum and water are evenly mixed in a ratio of 1:20, and the mixture is allowed to stand for 30 minutes and then filtered; washed phosphogypsum is obtained, and the washed phosphogypsum is calcined at 400°C for 5 hours to obtain calcined phosphogypsum; the calcined phosphogypsum is ground to obtain 60-80 mesh phosphogypsum fine powder.

[0074] Decrosslinking: EVA particles, phosphogypsum powder and antioxidant are mixed evenly, added to the HAAKE rheometer for decrosslinking, the rotor speed is set to 30r / min, and the decrosslinking is performed at 130°C for 15 minutes to obtain a decrosslinking mixture; the decrosslinking mixture contains decrosslinked EVA and phosphogypsum powder. The mass ratio of EVA particles, phosphogypsum powder and antioxidant is 70:30:1.

[0075] Internal mixing: pure EVA, decrosslinked mixture, crosslinking agent, stearic acid, zinc oxide and zinc stearate are added into an internal mixer for melt blending. The temperature of the internal mixer is set at 100°C, the speed is set at 30r / min, and the blending time is 20min to obtain a mixed rubber material; wherein, the component mass formula is as follows: 60 parts of pure EVA, 40 parts of decrosslinked EVA, 1.0 part of crosslinking agent, 1.3 parts of zinc oxide, 0.5 parts of stearic acid, 0.5 parts of zinc stearate, and 20 parts of SBS.

[0076] Hot pressing: putting the mixed rubber into a flat vulcanizer for hot pressing to obtain the EVA composite sheet; the temperature of the flat vulcanizer is set to 150° C., the time is 10 min, and the pressure is 10 MPa.

[0077] Example 2 Preparation of EVA composite sheet

[0078] The difference between Example 2 and Example 1 is that in the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum fine powder and antioxidant is 60:40:1.

[0079] Example 3 Preparation of EVA composite sheet

[0080] The difference between Example 3 and Example 1 is that in the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum powder and antioxidant is 80:20:1.

[0081] Example 4 Preparation of EVA composite sheet

[0082] The difference between Example 4 and Example 1 is that the phosphogypsum fine powder used is modified with stearic acid. The preparation method thereof is as follows: Preparation of phosphogypsum fine powder: phosphogypsum and water are mixed evenly in a ratio of 1:20, and then filtered after standing for 30 minutes; washed phosphogypsum is obtained, and the washed phosphogypsum is calcined at 400°C for 5 hours to obtain calcined phosphogypsum; the calcined phosphogypsum is ground to obtain 60-80 mesh ground phosphogypsum; 1 part by mass of ground phosphogypsum powder is put into 20 parts by mass of distilled water, and 3 parts by mass of stearic acid are added, and after ultrasonic modification at room temperature for 50-70 minutes, the phosphogypsum fine powder is filtered and dried.

[0083] Example 5 Preparation of EVA composite sheet

[0084] The difference between Example 5 and Example 1 is that:

[0085] 1) The phosphogypsum fine powder used is modified with stearic acid, and its preparation method is the same as that of Example 4.

[0086] 2) In the de-crosslinking step, the mass ratio of EVA granules, phosphogypsum powder and antioxidant is 60:40:1.

[0087] Example 6 Preparation of EVA composite sheet

[0088] The difference between Example 6 and Example 1 is that:

[0089] 1) The phosphogypsum fine powder used is modified with stearic acid, and its preparation method is the same as that of Example 4.

[0090] 2) In the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum powder and antioxidant is 80:20:1.

[0091] Example 7 Preparation of EVA composite sheet

[0092] The difference between Example 7 and Example 1 is that in the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum powder and antioxidant is 70:30:0.5.

[0093] Example 8 Preparation of EVA composite sheet

[0094] The difference between Example 8 and Example 1 is that in the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum powder and antioxidant is 70:30:0.7.

[0095] Example 9 Preparation of EVA composite sheet

[0096] The difference between Example 9 and Example 1 is that in the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum fine powder and antioxidant is 70:30:1.4.

[0097] Example 10 Preparation of EVA composite sheet

[0098] The difference between Example 10 and Example 1 is that in the mixing step, the amount of de-crosslinked EVA is 30 parts.

[0099] Example 11 Preparation of EVA composite sheet

[0100] The difference between Example 11 and Example 1 is that in the mixing step, the amount of de-crosslinked EVA is 50 parts.

[0101] Comparative Example 1 Preparation of EVA composite sheet

[0102] The difference between Comparative Example 1 and Example 1 is that in the de-crosslinking step, phosphogypsum is not added to de-crosslink EVA.

[0103] Comparative Example 2 Preparation of EVA composite sheet

[0104] The difference between Comparative Example 2 and Example 1 is that in the de-crosslinking step, no antioxidant is added to de-crosslink the EVA.

[0105] Comparative Example 3

[0106] Comparative Example 3 is different from Example 1 in that no de-crosslinking step is performed, and the pelletized EVA pellets are directly used instead of the de-crosslinking mixture for banburying.

[0107] Granulation: The discarded EVA sole material (EVA midsole after scrapping sports shoes) is washed with clean water for the first time for 20 minutes, and then placed in a blast drying oven for drying; then the EVA sole is crushed into particles with a particle size of 4mm using a crusher, and the EVA particles are washed with 60%-70% alcohol for the second time, and dried to obtain EVA granular materials;

[0108] Internal mixing: pure EVA, EVA granules, cross-linking agent, stearic acid, zinc oxide and zinc stearate are added into an internal mixer for melt blending. The temperature of the internal mixer is set at 100°C, the speed is set at 30r / min, and the blending time is 20min to obtain a mixed rubber material; wherein, the component mass formula is as follows: 60 parts of pure EVA, EVA granules, 1.0 parts of cross-linking agent, 1.3 parts of zinc oxide, 0.5 parts of stearic acid, 0.5 parts of zinc stearate, and 20 parts of SBS.

[0109] Hot pressing: putting the mixed rubber into a flat vulcanizer for hot pressing to obtain the EVA composite sheet; the temperature of the flat vulcanizer is set to 150° C., the time is 10 min, and the pressure is 10 MPa.

[0110] The performance of the EVA composite sheets prepared in Examples 1-11 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1:

[0111] Table 1 EVA composite sheet performance test results

[0112]

[0113] As can be seen from Table 1, with the increase of the proportion of unmodified and modified phosphogypsum (Examples 1-3 and 4-6) and the increase of the proportion of antioxidant (Examples 1, 7-9-8), the gel content of the sample gradually decreases. This shows that the addition of phosphogypsum and antioxidant in the present invention can effectively improve the de-crosslinking of waste EVA. At the same time, the EVA composite sheet prepared by adding modified phosphogypsum shows better physical and mechanical properties than Examples 1-3 and Comparative Examples 1-3, and the impact strength, tensile strength and elongation at break are greatly improved.

[0114] The invention provides a new method for high-value recycling of waste EVA shoe materials, is beneficial to resource regeneration of EVA de-crosslinking products, and is industrially applied in sports shoe soles.

[0115] Finally, it should be noted that although the above embodiments have been described in the text of the specification of this application, this does not limit the scope of patent protection of this application. All technical solutions generated by replacing or modifying equivalent structures or equivalent processes based on the essential concept of this application using the contents recorded in the text of the specification of this application, as well as directly or indirectly implementing the technical solutions of the above embodiments in other related technical fields, are included in the scope of patent protection of this application.

Claims

1. A method for preparing an EVA composite sheet, characterized in that: The preparation of the EVA composite sheet comprises the following steps: Pelletizing: Wash and pelletize the recovered waste EVA to obtain EVA pellets; Decrosslinking: the EVA particles, phosphogypsum powder and antioxidant are mixed evenly, and added into a rheometer for decrosslinking to obtain a decrosslinking mixture; the decrosslinking mixture comprises decrosslinking EVA and phosphogypsum powder; the decrosslinking temperature is <160°C; Internal mixing: pure EVA, de-crosslinking mixture, crosslinking agent, stearic acid, zinc oxide and zinc stearate are added into an internal mixer for melting and blending to obtain a mixed rubber material; the internal mixing temperature is less than 160°C; Hot pressing: putting the mixed rubber into a flat vulcanizer for hot pressing at a temperature of less than 160° C. to obtain the EVA composite sheet.

2. The preparation method according to claim 1, characterized in that: In the pelletizing step, the size of the EVA pellets is 2-8 mm.

3. The preparation method according to claim 1, characterized in that: In the de-crosslinking step, the phosphogypsum fine powder is prepared by washing and calcining the phosphogypsum and then grinding it, and the mesh size of the phosphogypsum fine powder is 60-80 meshes.

4. The preparation method according to claim 3, characterized in that: The preparation of the phosphogypsum fine powder also includes a modification step: adding the washed, calcined and ground phosphogypsum and stearic acid into water for ultrasonic modification.

5. The preparation method according to claim 1, characterized in that: In the de-crosslinking step, the mass ratio of EVA particles, phosphogypsum fine powder and oxidant is 60-80:20-40:0.5-1.

4.

6. The preparation method according to claim 1, characterized in that: In the de-crosslinking step, the de-crosslinking temperature is 120-140°C.

7. The preparation method according to claim 1, characterized in that: The banburying step comprises the following components in parts by weight: 50-70 parts by weight of pure EVA, 30-50 parts by weight of de-crosslinked EVA, 0.8-1.2 parts by weight of a crosslinking agent, 1.0-1.5 parts by weight of zinc oxide, 0.3-0.7 parts by weight of stearic acid, and 0.3-0.7 parts by weight of zinc stearate.

8. The preparation method according to claim 6, characterized in that: The mixing step further comprises 16-24 parts by weight of SBS.

9. The preparation method according to claim 1, characterized in that: In the banburying step, the banburying temperature is 100-120°C.

10. An EVA composite sheet, characterized in that: The EVA composite sheet is prepared by the preparation method described in any one of claims 1-9.